Dispersive nonwoven materials containing CMC-based binders

JP7651554B2Active Publication Date: 2025-03-26GLATFELTER CORP
View PDF 82 Cites 0 Cited by

Patent Information

Application Number
JP2022508463
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-08
Filing Date
2020-08-05
Publication Date
2025-03-26
Estimated Expiration
2040-08-05

AI Technical Summary

Benefits of technology

【0018】 前述では、以下の詳細な記載がよりよく理解され得るように本出願の特色及び技術的な利点を広く概説した。本出願の特許請求の範囲の主題を形成する、本出願の追加の特色及び利点は、以下に記載される。開示される概念及び特定の実施形態が、本出願の同一の目的を実行するための他の構造体を修飾又は設計する基礎として容易に利用され得ることは当業者に認識されるべきである。また、そのような等価構造が、添付された特許請求の範囲において述べられる本出願の趣旨及び範囲から逸脱しないことも当業者によって了解されるべきである。本出願の特徴であると考えられる新規の特色は、その構成及び操作の方法の両方に関して、更なる対象及び利点と一緒に、以下の記載から一層よく理解されよう。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651554000019
    Figure 0007651554000019
  • Figure 0007651554000020
    Figure 0007651554000020
  • Figure 0007651554000021
    Figure 0007651554000021
Patent Text Reader

Abstract

A nonwoven material is provided having at least one layer comprising cellulose fibers, synthetic fibers, or a combination thereof. Such a nonwoven material has a surface at least partially coated with a binder comprising carboxymethyl cellulose (CMC) and a metal salt and having a pH of about 4.3 to about 4.5. Nonwoven materials containing such a binder provide increased wet strength and dispersibility and are suitable for use in a variety of applications, including wipes.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Dispersible nonwoven materials bonded with carboxymethyl cellulose (CMC)-based binders containing metal salts are provided. Such nonwoven materials can be used in a variety of applications and can have improved wet strength and dispersibility. [Background technology]

[0002] Dispersible nonwoven products such as wipes are widely used, providing relatively inexpensive hygienic convenience for use in many applications. Several attempts have been made to produce washable, dispersible products that are sufficiently robust for their intended purposes, yet are suitably disposable.

[0003] One such approach is to incorporate water-soluble or redispersible polymeric binders to make wet wipes.The technical problems associated with wet wipes and wet tissues using such binders include providing sufficient binder to nonwoven materials to provide the necessary dry tensile strength and wet tensile strength for their intended use, while at the same time protecting the dispersible binder from dissolving in aqueous environment during storage.Furthermore, wipe materials need to be easily dispersible and appropriately disposable while having the necessary dry tensile strength and wet tensile strength.

[0004] Such water-soluble binders are disclosed, for example, in U.S. Patent No. 5,281,306 to Kakiuchi et al. Kakiuchi et al. provide an aqueous cleaner that includes a water-soluble binder having carboxyl groups, at least one metal ion, and an organic solvent to provide a dispersible material. However, there is a continuing need for improved binder applications that simultaneously provide acceptable strength and dispersibility in nonwoven materials. The subject matter of the present disclosure addresses these and other needs. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] U.S. Patent No. 5,281,306 [Patent Document 2] U.S. Patent No. 6,562,743 [Patent Document 3] U.S. Patent No. 8,946,100 [Patent Document 4] U.S. Patent No. 6,241,713 [Patent Document 5] U.S. Patent No. 6,353,148 [Patent Document 6] U.S. Patent No. 6,171,441 [Patent Document 7] U.S. Patent No. 6,159,335 [Patent Document 8] U.S. Patent No. 5,695,486 [Patent Document 9] U.S. Patent No. 6,344,109 [Patent Document 10] U.S. Patent No. 5,068,079 [Patent Document 11] U.S. Patent No. 5,492,759 [Patent Document 12] U.S. Patent No. 5,269,049 [Patent Document 13] U.S. Patent No. 5,601,921 [Patent Document 14] U.S. Patent No. 5,693,162 [Patent Document 15] U.S. Patent No. 5,922,163 [Patent Document 16] U.S. Patent No. 6,007,6536 [Patent Document 17] U.S. Patent No. 6,355,079 [Patent Document 18] U.S. Patent No. 6,403,857 [Patent Document 19] U.S. Patent No. 6,479,415 [Patent Document 20] U.S. Patent No. 6,562,742 [Patent Document 21] U.S. Patent No. 6,559,081 [Patent Document 22] U.S. Patent No. 6,495,734 [Patent Document 23] U.S. Patent No. 6,420,626 [Patent Document 24] US Patent Application Publication No. 2004 / 0208175 [Patent Document 25] US Patent Application Publication No. 2002 / 0013560 [Patent Document 26] U.S. Patent No. 4,432,833 [Patent Document 27] U.S. Patent No. 4,425,186 [Patent Document 28] U.S. Patent No. 5,776,308 [Patent Document 29] U.S. Patent No. 4,098,996 [Patent Document 30] U.S. Patent No. 5,547,541 [Patent Document 31] U.S. Patent No. 4,731,269 [Patent Document 32] U.S. Patent No. 4,950,541 [Patent Document 33] U.S. Patent No. 5,082,899 [Patent Document 34] U.S. Patent No. 5,126,199 [Patent Document 35] U.S. Patent No. 5,372,885 [Patent Document 36] U.S. Patent No. 5,456,982 [Patent Document 37] U.S. Patent No. 5,705,565 [Patent Document 38] U.S. Patent No. 2,861,319 [Patent Document 39] U.S. Patent No. 2,931,091 [Patent Document 40] U.S. Patent No. 2,989,798 [Patent Document 41] U.S. Patent No. 3,038,235 [Patent Document 42] U.S. Patent No. 3,081,490 [Patent Document 43] U.S. Patent No. 3,117,362 [Patent Document 44] U.S. Patent No. 3,121,254 [Patent Document 45] U.S. Patent No. 3,188,689 [Patent Document 46] U.S. Patent No. 3,237,245 [Patent Document 47] U.S. Patent No. 3,249,669 [Patent Document 48] U.S. Patent No. 3,457,342 [Patent Document 49] U.S. Patent No. 3,466,703 [Patent Document 50] U.S. Patent No. 3,469,279 [Patent Document 51] U.S. Patent No. 3,500,498 [Patent Document 52] U.S. Patent No. 3,585,685 [Patent Document 53] U.S. Patent No. 3,163,170 [Patent Document 54] U.S. Patent No. 3,692,423 [Patent Document 55] U.S. Patent No. 3,716,317 [Patent Document 56] U.S. Patent No. 3,778,208 [Patent Document 57] U.S. Patent No. 3,787,162 [Patent Document 58] U.S. Patent No. 3,814,561 [Patent Document 59] U.S. Patent No. 3,963,406 [Patent Document 60] U.S. Patent No. 3,992,499 [Patent Document 61] U.S. Patent No. 4,052,146 [Patent Document 62] U.S. Patent No. 4,251,200 [Patent Document 63] U.S. Patent No. 4,350,006 [Patent Document 64] U.S. Patent No. 4,370,114 [Patent Document 65] U.S. Patent No. 4,406,850 [Patent Document 66] U.S. Patent No. 4,445,833 [Patent Document 67] U.S. Patent No. 4,717,325 [Patent Document 68] U.S. Patent No. 4,743,189 [Patent Document 69] U.S. Patent No. 5,162,074 [Patent Document 70] U.S. Patent No. 5,256,050 [Patent Document 71] U.S. Patent No. 5,505,889 [Patent Document 72] U.S. Patent No. 5,582,913 [Patent Document 73] U.S. Patent No. 6,670,035 [Patent Document 74] U.S. Patent No. 3,972,092 [Non-patent literature]

[0006] [Non-Patent Document 1] Watson, P. et al., Canadian Pulp Fibre Morphology: Superiority and Considerations for End Use Potential, The Forestry Chronicle, Vol. 85, No. 3, pp. 401-408, May / June 2009. [Non-Patent Document 2] Horn, R., Morphology of Pulp Fiber from Hardwoods and Influence on Paper Strength, Research Paper FPL 312, Forest Products Laboratory, US Department of Agriculture (1978) and Bleached Eucalyptus Kraft Pulp ECF Technical Sheet (April 2017) (https: / / www.metsafibre.com / en / Documents / Data-sheets / Cenibra-euca-Eucalyptus.pdf) [Non-Patent Document 3] AJ Stamm, Forest Products Journal 5(6):413 pages, 1955 Summary of the Invention [Means for solving the problem]

[0007] The subject matter of the present disclosure provides a nonwoven material at least partially coated with a carboxymethyl cellulose (CMC) based binder that includes a metal salt. Surprisingly and advantageously, it has been found that the binder of the present disclosure provides a nonwoven material having both high wet strength and fast dispersibility at a pH of about 4.3 to about 4.5.

[0008] The present disclosure provides a nonwoven material. The nonwoven material can include at least one layer including cellulose fibers, synthetic fibers, or a combination thereof. The at least one layer can be coated with a binder on at least a portion of its surface. The binder can include carboxymethylcellulose (CMC) and a metal salt. The binder can have a pH of about 4.3 to about 4.5.

[0009] In certain embodiments, the binder can have a pH of about 4.3 to about 4.4, or about 4.4 to about 4.5.

[0010] In certain embodiments, the CMC and metal salt may be present in the binder in a ratio of about 1:1 or about 3:1.

[0011] In certain embodiments, the metal salt can include calcium chloride.

[0012] In certain embodiments, the binder can further comprise a surfactant.

[0013] In certain embodiments, the plasticizer can include polyethylene glycol.

[0014] In certain embodiments, the cellulosic fibers may include softwood fibers, hardwood fibers, or a combination thereof.

[0015] In certain embodiments, the synthetic fibers may include bicomponent fibers.

[0016] In some embodiments, the nonwoven material can have a wet strength of from about 350 gli to about 400 gli.

[0017] The present disclosure provides a wipe comprising the nonwoven material of the present disclosure and a lotion. The present disclosure further provides a personal care product comprising the nonwoven material of the present disclosure.

[0018] The foregoing has outlined broadly the features and technical advantages of the present application in order that the detailed description that follows may be better understood. Additional features and advantages of the present application which form the subject of the claims of the present application are described below. It should be appreciated by those skilled in the art that the conception and specific embodiments disclosed may be readily utilized as a basis for modifying or designing other structures for carrying out the same purposes of the present application. It should also be realized by those skilled in the art that such equivalent constructions do not depart from the spirit and scope of the present application as set forth in the appended claims. The novel features believed to be characteristic of the present application, both as to its organization and method of operation, together with further objects and advantages, will be better understood from the following description. [Brief description of the drawings]

[0019] [Figure 1] 1 shows wet strength test results of cellulosic nonwoven materials containing cationic and anionic lotion agents and binders at various levels of pH, prepared according to certain non-limiting embodiments provided in Example 1. [Figure 2A] 1 shows wet strength test results for cellulosic nonwoven materials containing binders at various levels of pH with alcohol, prepared according to certain non-limiting embodiments provided in Example 1. [Figure 2B] 1 shows wet strength test results of nonwoven materials containing binders at various levels of pH prepared according to certain non-limiting embodiments provided in Example 1. [Diagram 3] 1 shows wet strength test results of nonwoven materials containing binders at various levels of pH prepared according to certain non-limiting embodiments provided in Example 1. [Figure 4] 1 shows wet strength test results of various nonwoven materials containing a binder prepared according to certain non-limiting embodiments provided in Example 2. [Figure 5A] 1 shows wet strength test results of modified cellulosic nonwoven materials with binders prepared according to certain non-limiting embodiments provided in Example 4. [Figure 5B] 1 shows wet strength test results of modified cellulosic nonwoven materials with binders prepared according to certain non-limiting embodiments provided in Example 4. [Figure 6A] 1 shows wet strength test results of a nonwoven material containing a binder, which may be prepared with a surfactant and a plasticizer according to certain non-limiting embodiments provided in Example 6. [Figure 6B] 1 shows wet strength test results of a nonwoven material containing a binder, which may be prepared with a surfactant and a plasticizer according to certain non-limiting embodiments provided in Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The presently disclosed subject matter provides a nonwoven material comprising at least one layer of cellulose fibers, synthetic fibers, or a combination thereof. The nonwoven material is at least partially coated with a binder comprising carboxymethylcellulose (CMC) and a metal salt. The binder of the present disclosure can be applied to the nonwoven material at a pH of about 4.3 to about 4.5. Such nonwoven materials comprising the binder of the present disclosure can simultaneously improve wet strength and dispersibility. The presently disclosed subject matter also provides a method of making such a material. These and other aspects of the presently disclosed subject matter are discussed in more detail in the detailed description and examples.

[0021] definition The terms used herein have their ordinary meanings in the art, generally within the context of this subject matter and in the specific context in which each term is used. Certain terms are defined below to provide additional guidance in describing the compositions and methods of the presently disclosed subject matter, and how to make and use the same.

[0022] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to a "compound" includes a mixture of compounds.

[0023] The term "about" or "approximately" means within an acceptable error range for a particular value as determined by one of ordinary skill in the art, which depends in part on the method by which the value is measured or determined, i.e., the limitations of the measurement system. For example, "about" may mean within 3 or more than 3 standard deviations, according to the practice of the art. Alternatively, "about" may mean within a range of up to 20%, preferably up to 10%, more preferably up to 5%, and even more preferably up to 1% of a given value. Alternatively, particularly with respect to a system or method, the term may mean within an order of magnitude of a value, preferably within a 5-fold range, and more preferably within a 2-fold range.

[0024] The term "basis weight" as used herein refers to the amount by mass of a compound over a given area. Examples of units of measurement include grams per square meter, identified by the acronym "gsm."

[0025] As used herein, the term "cellulose" or "cellulosic" includes any material having cellulose as a major component, specifically containing at least 50 percent by weight cellulose or cellulose derivatives. Thus, the term includes cotton, ordinary wood pulp, cellulose acetate, rayon, thermochemical wood pulp, chemical wood pulp, debonded chemical wood pulp, milkweed floss, microcrystalline cellulose, microfibrillated cellulose, and the like.

[0026] As used herein, the phrase "chemical modification", when used in reference to fibers, means that the fibers are treated with a polyvalent metal-containing compound to produce fibers that contain a polyvalent metal-containing compound bound thereto. It is not necessary for the compound to be chemically bound to the fibers, but it is preferred that the compound remain in close association with the fibers by coating, adhesion, precipitation, or any other mechanism so that the compound does not migrate from the fibers during normal handling of the fibers. In particular, the compound can remain associated with the fibers even when wetted or washed with a liquid. For convenience, the association between the fibers and the compound can be referred to as a bond, and the compound can be said to be bound to the fibers.

[0027] As used herein, the terms "fibrous" or "fibrous" refer to granular materials having a ratio of length to diameter of such granular material greater than about 10. Conversely, "non-fibrous" or "non-fibrous" materials are meant to refer to granular materials having a ratio of length to diameter of such granular material of about 10 or less.

[0028] As used herein, "nonwoven" refers to a type of material, including but not limited to textiles or plastics. A nonwoven is a sheet or web structure made of fibers, filaments, fused plastics, or plastic films mechanically, thermally, or chemically bonded together. A nonwoven is a fabric made directly from a web of fibers, without the yarn preparation required for weaving or knitting. In a nonwoven, the collection of fibers is held together by one or more of the following: (1) by mechanical interlocking in a random web or mat; (2) by fusion of the fibers; or (3) by bonding with a bonding medium such as a natural or synthetic resin or binder.

[0029] As used herein, the term "weight percent" is meant to refer to either (i) the amount by weight of a component / ingredient in a material as a weight percentage of a layer of material; or (ii) the amount by weight of a component / ingredient in a material as a weight percentage of the final microfiber wipe material or product.

[0030] fiber The nonwoven material of the subject matter of the present disclosure comprises fibers. The fibers may be natural, synthetic, or a mixture thereof. In some embodiments, the fibers may be cellulosic fibers, one or more synthetic fibers, or a mixture thereof. In some embodiments, the nonwoven material of the present disclosure may comprise layers of different cellulosic fibers. In some embodiments, the different cellulosic fibers may be blended together in one or more layers of the nonwoven material.

[0031] Cellulose Fiber Any naturally occurring cellulose fiber known in the art may be used in the cellulosic layer, including those derived from wood pulp or regenerated cellulose. In certain embodiments, the cellulose fibers include digested fibers, such as, but not limited to, kraft fibers, prehydrolyzed kraft fibers, soda fibers, sulfite fibers, chemothermo-mechanical fibers, and thermomechanically treated fibers, derived from softwoods, hardwoods, or cotton linters. In other embodiments, the cellulose fibers include, but are not limited to, kraft digested fibers, including prehydrolyzed kraft digested fibers. Non-limiting examples of cellulose fibers suitable for use in the present subject matter are cellulose fibers derived from softwoods, such as pine, fir, and spruce. Other suitable cellulose fibers include, but are not limited to, those derived from esparto grass, bagasse, kemp, flax, hemp, kenaf, and other woody and cellulosic fiber sources. Suitable cellulose fibers include, but are not limited to, bleached kraft southern pine fibers sold under the trademark FOLEY FLUFFS® (Buckeye Technologies Inc., Memphis, Tenn.). Additionally, fibers sold under the trademark CELLU TISSUE® (eg, Grade 3024) (Clearwater Paper Corporation, Spokane, Wash.) find use in certain embodiments of the subject matter of the present disclosure.

[0032] The nonwoven material of the subject matter of the present disclosure may include, but is not limited to, commercially available bright fluff pulps, including but not limited to southern softwood kraft (e.g., Golden Isles® 4725 from GP Cellulose) or southern softwood fluff pulp (e.g., Treated FOLEY FLUFFS®), northern softwood sulfite pulp (e.g., T730 from Weyerhaeuser), or hardwood pulp (e.g., eucalyptus). In some embodiments, the nonwoven material may include eucalyptus fibers (Suzano, untreated). While certain pulps may be preferred based on various factors, any absorbent fluff pulp or mixtures thereof may be used. In some embodiments, wood cellulose, cotton linter pulp, chemically modified cellulose, such as crosslinked cellulose fibers, and highly refined cellulose fibers may be used. Further non-limiting examples of pulps are FOLEY FLUFFS® FFTAS (also known as FFTAS or Buckeye Technologies FFT-AS pulp) and Weyco CF401.

[0033] In some embodiments, fine fibers, such as certain softwood fibers, can be used. Some non-limiting examples of such fine fibers, including pulp coarseness, are provided in Table I below with reference to Watson, P. et al., Canadian Pulp Fibre Morphology: Superiority and Considerations for End Use Potential, The Forestry Chronicle, Vol. 85, No. 3, pp. 401-408, May / June 2009.

[0034] [Table 1]

[0035] In some embodiments, fine fibers such as certain hardwood fibers can be used. Some non-limiting examples of such fine fibers, including pulp coarseness, are provided in Table II, at least in part, by reference to Horn, R., Morphology of Pulp Fiber from Hardwoods and Influence on Paper Strength, Research Paper FPL 312, Forest Products Laboratory, US Department of Agriculture (1978) and Bleached Eucalyptus Kraft Pulp ECF Technical Sheet (April 2017), available at: https: / / www.metsafibre.com / en / Documents / Data-sheets / Cenibra-euca-Eucalyptus.pdf. In certain embodiments, eucalyptus pulp can be used.

[0036] [Table 2]

[0037] In certain embodiments of the subject matter of the present disclosure, the following celluloses are used: GP4723, fully treated pulp (Leaf River) (available from Georgia-Pacific); GP4725, semi-treated pulp (available from Georgia-Pacific); Tencel (available from Lenzing); cellulose flax fiber; Danufil (available from Kelheim); Viloft (available from Kelheim); GP4865, odor-controlled semi-treated pulp (available from Georgia-Pacific); Grade 3024 Cellu Tissue (available from Clearwater); Brawny Industrial Flax 500 (available from Georgia-Pacific). The nonwoven material of the present disclosure can include cellulose fibers. In some embodiments, one or more layers of the nonwoven material can include cellulose fibers of about 5 gsm to about 150 gsm, about 5 gsm to about 100 gsm, or about 10 gsm to about 50 gsm. In certain embodiments, one or more layers may comprise about 60 gsm, about 65 gsm, or about 70 gsm cellulosic fibers.

[0038] Chemically modified cellulose fibers The subject matter of the present disclosure contemplates the use of chemically modified cellulosic fibers. As embodied herein, cellulosic fibers can be chemically treated with compounds containing polyvalent metal ions, such as polyvalent cations. Such chemically modified fibers are described, by way of illustration and not limitation, in U.S. Pat. Nos. 6,562,743 and 8,946,100, the contents of which are incorporated herein by reference in their entirety. Chemically modified cellulosic fibers can optionally be associated with a weak acid. For example, suitable modified cellulosic fibers include aluminum modified FFLE+ fiber from GP Cellulose or Valance from International Paper.

[0039] The chemically modified cellulose fibers can be treated with from about 0.1 weight percent to about 20 weight percent of the polyvalent cation-containing compound based on the dry weight of the untreated fibers, desirably with from about 2 weight percent to about 12 weight percent of the polyvalent metal-containing compound, or alternatively with from about 3 weight percent to about 8 weight percent of the polyvalent cation-containing compound based on the dry weight of the untreated fibers.

[0040] Any polyvalent metal salt, including transition metal salts, can be used, provided that the compound is capable of increasing the stability of cellulose fibers in an alkaline environment. Examples of suitable polyvalent metals include beryllium, magnesium, calcium, strontium, barium, titanium, zirconium, vanadium, chromium, molybdenum, tungsten, manganese, iron, cobalt, nickel, copper, zinc, aluminum, and tin. In some embodiments, the ions include aluminum, iron, and tin. In some embodiments, the metal ions have an oxidation state of +3 or +4. In some embodiments, the polyvalent metal is aluminum. Any salt containing a polyvalent metal ion can be used. Examples of suitable inorganic salts of the above metals include chlorides, nitrates, sulfates, borates, bromides, iodides, fluorides, nitrides, perchlorates, phosphates, hydroxides, sulfides, carbonates, bicarbonates, oxides, alkoxides, phenoxides, phosphites, and hypophosphites. Examples of suitable organic salts of the above metals include formates, acetates, butyrates, hexanoates, adipates, citrates, lactates, oxalates, propionates, salicylates, glycinates, tartrates, glycolates, sulfonates, phosphonates, glutamates, octanoates, benzoates, gluconates, maleates, succinates, and 4,5-dihydroxy-benzene-1,3-disulfonates. In addition to polyvalent metal salts, other compounds such as complexes of the above salts include amines, ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DIPA), nitrilotriacetic acid (NTA), 2,4-pentanedione, and ammonia. In some embodiments, the polyvalent metal salt is aluminum chloride, aluminum hydroxide, or aluminum sulfate. Alum is a water-soluble aluminum sulfate salt. In aqueous slurries of cellulose, some of the alum penetrates the cell walls of the fibers, but the concentration of the ions is low so that most of the dissolved aluminum salts are on the exterior of the fibers. When the pH is adjusted to precipitate aluminum hydroxide, most of the precipitate adheres to the fiber surface.

[0041] In some embodiments, the chemically modified cellulose fibers have an acid bound or associated therewith. A variety of suitable acids can be used. In some embodiments, the acid has low volatility. In some embodiments, the acid is a weak acid. For example, without limitation, suitable acids include inorganic acids such as sodium hydrogen sulfate, sodium dihydrogen phosphate and disodium hydrogen phosphate, and organic acids such as formic acid, acetic acid, aspartic acid, propionic acid, butyric acid, hexanoic acid, benzoic acid, gluconic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, tartaric acid, maleic acid, malic acid, phthalic acid, sulfonic acid, phosphonic acid, salicylic acid, glycolic acid, citric acid, butanetetracarboxylic acid (BTCA), octanoic acid, polyacrylic acid, polysulfonic acid, polymaleic acid and lignosulfonic acid, as well as hydrolyzed polyacrylamide and CMC (carboxymethylcellulose). Among the carboxylic acids, acids with two carboxyl groups are preferred, and acids with three carboxyl groups are more preferred. In some embodiments, the acid is citric acid.

[0042] In general, the amount of acid used may depend on the acidity and the molecular weight of the acid. In some embodiments, the acid comprises between about 0.5 weight percent of the fiber and about 10 weight percent of the fiber. As used herein, "weight percent of the fiber" refers to the weight percent of the dry fiber treated with the polyvalent metal-containing compound (i.e., based on the dry weight of the treated fiber). For example, in some embodiments, the acid is citric acid in an amount between about 0.5 weight percent of the fiber and about 3 weight percent of the fiber. An alternative combination is an aluminum-containing compound and citric acid. For chemically treated fibers of this aspect of the disclosure, it is desirable for the weak acid content of the chemically treated fiber to be between about 0.5 weight percent and about 10 weight percent based on the dry weight of the treated fiber, more desirably between about 0.5 weight percent and about 5 weight percent based on the dry weight of the treated fiber, or between about 0.5 weight percent and about 3 weight percent based on the dry weight of the treated fiber.

[0043] Alternatively, in some embodiments, a buffer salt can be used in place of the weak acid combined with the polyvalent metal-containing compound. Any buffer salt that gives a solution with a pH of less than about 7 in water is suitable. For example, without limitation, suitable buffer salts include sodium acetate, sodium oxalate, sodium tartrate, sodium phthalate, sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium borate. Buffer salts can be used in combination with their acids in combinations that give a solution with a pH of less than about 7 in water, for example, oxalic acid / sodium oxalate, tartaric acid / sodium tartrate, sodium phthalate / phthalic acid, and sodium dihydrogen phosphate / disodium hydrogen phosphate.

[0044] In a further variation, the polyvalent metal-containing compound can be used in combination with an insoluble metal hydroxide, such as, for example, magnesium hydroxide, or in combination with one or more alkaline-stable antioxidant chemicals or alkaline-stable reducing agents that inhibit fiber degradation in alkaline oxygen environments. Examples include inorganic chemicals, such as sodium sulfite, and organic chemicals, such as hydroquinone.

[0045] For chemically modified cellulose fibers, it is desirable for the buffer salt content, buffer salt-weak acid combination content, insoluble metal hydroxide content, and / or antioxidant content of the chemically treated fiber to be from about 0.5 weight percent to about 10 weight percent based on the dry weight of the treated fiber, more desirably from about 0.5 weight percent to about 5 weight percent based on the dry weight of the treated fiber, or from about 0.5 weight percent to about 3 weight percent based on the dry weight of the treated fiber.

[0046] In some embodiments, reducing agents can be applied to modified cellulose fibers to maintain a desired level of fiber brightness by reducing brightness reversion. The addition of acidic materials can cause browning of the fibers when heated during processing of a web containing the fibers. The reducing agent counters the browning of the fibers. The reducing agent can also bind to the fibers. Suitable reducing agents include sodium hypophosphite, sodium bisulfite, and mixtures thereof.

[0047] Fibers suitable for use in the practice of the present disclosure can be treated in a variety of ways that bring the polyvalent metal ion-containing compound into intimate association with the fiber. In some embodiments, the compound is introduced into a solution containing the fiber in a slurry form, causing precipitation of the compound on the surface of the fiber. Alternatively, the fiber can be sprayed with the compound in an aqueous or non-aqueous solution or suspension. The fiber can be treated while in the singulated state or in the form of a web. For example, the compound can be applied directly to the fiber in a powder or other physical form. However, whatever method is used, it is preferred that the compound remains bound to the fiber before the fiber comes into contact with the liquid, so that the compound does not migrate during normal physical handling of the fiber.

[0048] In an embodiment, the treated fibers of the present disclosure are made from cellulose fibers known as FOLEY FLUFFS® manufactured by GP Cellulose. The pulp is slurried, the pH is adjusted to about 4.0, and aluminum sulfate (Al2(SO4)3) in an aqueous solution is added to the slurry. The slurry is agitated and the consistency is reduced. While agitating, the pH of the slurry is raised to approximately 5.7. The fibers are then formed into a web or sheet, dried, and optionally sprayed with a solution of citric acid at a loading of about 2.5 weight percent of the fibers. The web is then packaged and shipped to end users for further processing, including fiberization, to form individualized fibers useful in the fabrication of various products.

[0049] In another embodiment, the treated fibers of the present disclosure are made from cellulose fibers obtained from GP Cellulose. The pulp is slurried, the pH is adjusted to about 4.0, and aluminum sulfate (Al2(SO4)3) in an aqueous solution is added to the slurry. The slurry is agitated and the consistency is reduced. While agitating, the pH of the slurry is raised to approximately 5.7. The fibers are then formed into a web or sheet, dried, and sprayed with a solution of sodium oleate at a loading of about 1.0 weight percent of the fibers. The web is then packaged and shipped to an end user for further processing, including reslurrying, to form a web useful in the fabrication of filtration products. If a reducing agent is to be applied, it can be applied before the drying step and after the other application steps. The reducing agent can be applied by spraying, painting, or foaming.

[0050] Metal ion content, including aluminum or iron content, in pulp samples can be determined by wet ashing (oxidizing) the samples with nitric acid and perchloric acid in a digester. A blank is run by oxidizing the same process as the samples. The samples are then analyzed using an inductively coupled plasma spectrophotometer, such as, for example, a Perkin-Elmer ICP 6500. From the analysis, the ion content in the sample can be determined in parts per million. The polyvalent cation content is desirably about 0.1 weight percent to about 5.0 weight percent based on the dry weight of the treated fiber, more desirably about 0.1 weight percent to about 3.0 weight percent based on the dry weight of the treated fiber, or about 0.1 weight percent to about 1.5 weight percent based on the dry weight of the treated fiber, or about 0.2 weight percent to about 0.9 weight percent based on the dry weight of the treated fiber, or about 0.3 weight percent to about 0.8 weight percent based on the dry weight of the treated fiber.

[0051] Without intending to be bound by theory, it is believed that by this process, soluble Al2(SO4)3 introduced into the pulp slurry is converted to insoluble Al(OH)3 as the pH is increased. The insoluble aluminum hydroxide precipitates on the fibers. Thus, the resulting chemically treated cellulose fibers are coated with Al(OH)3 or contain the insoluble metal within the fibers.

[0052] Sodium oleate sprayed onto a web containing fibers dries on the fibers. When the Al(OH)3 oleate treated fibers are formed into a filter base sheet, the aluminum and oleate ions create a hydrophobic environment in addition to improving the wet strength of the structure. These results are illustrated in the procedure set out below.

[0053] In another embodiment, the hydrated aluminum sulfate and sodium oleate are sprayed onto the fibers after the dry section of the paper machine. In another embodiment, the hydrated aluminum sulfate and sodium oleate are precipitated onto the fibers in the wet finish section of the paper machine. In another embodiment, the hydrated aluminum sulfate and sodium hypophosphite are sprayed onto the fibers before the press stage, and the sodium oleate is sprayed after drying. In another embodiment, the hydrated aluminum sulfate, sodium hypophosphite, and sodium oleate are sprayed onto the fibers before the press stage. In yet another embodiment, the hydrated aluminum sulfate is precipitated onto the fibers, the hydrated aluminum hypophosphite and sodium hypophosphite are sprayed onto the fibers before pressing, and the sodium oleate is sprayed onto the fibers after drying. In another embodiment, the hydrated aluminum sulfate is precipitated onto the fibers, and the sodium oleate is sprayed onto the fibers before the press stage.

[0054] Various materials, structures and fabrication processes are described, by way of example and not limitation, in U.S. Pat. Nos. 6,241,713, 6,353,148, 6,353,148, 6,171,441, 6,159,335, 5,695,486, 6,344,109, 5,068,079, 5,492,759, 5,269,049, 5,601,921, 5,693,162, 5,927, 5,102, 5,106, 5,108, 5,110, 5,120, 5,130, 5,140, ​​5,152, 5,166, 5,170, 5,172, 5,180, 5,182, 5,190, 5,200, 5,200, 5,210, 5,220, 5,230, 5,240, 5,250, 5,260, 5,270, 5,280, 5,290, 6,300, 6,310, 6,320, 6,330, 6,400, 6,410, 6,420, 6,560, 6,580, 6,620, 6,700, 6,720, 6,840, 6,900, 6,100, 6,120, 6,130, 6,240, 6,350, 6,450, 6,560, 6,620, 6,700, 6,140, Nos. 22,163, 6,007,653, 6,355,079, 6,403,857, 6,479,415, 6,562,742, 6,562,743, 6,559,081, 6,495,734, 6,420,626, and 8,946,100, as well as U.S. Patent Application Publication Nos. 2004 / 0208175 and 2002 / 0013560.

[0055] In some embodiments, chemically modified cellulose, such as cross-linked cellulose fibers, and highly purified cellulose fibers can be used. In certain embodiments, the modified cellulose fibers are cross-linked cellulose fibers. In some embodiments, the modified cellulose fibers include a polyhydroxy compound. Non-limiting examples of polyhydroxy compounds include glycerin, trimethylolpropane, pentaerythritol, polyvinyl alcohol, partially hydrolyzed polyvinyl acetate, and fully hydrolyzed polyvinyl acetate.

[0056] In some embodiments, the modified cellulose pulp fibers are softened or plasticized and are inherently more compressible than unmodified pulp fibers. The same pressure applied to a plasticized pulp web results in a higher density than when applied to an unmodified pulp web. Furthermore, a densified web of plasticized cellulose fibers is inherently softer than a similarly dense web of unmodified fibers of the same wood type. Softwood pulp can be made more compressible using cationic surfactants as debonding agents to break intrafiber associations. The use of one or more debonding agents facilitates the disintegration of the pulp sheet into fluff during the airlaid process. Examples of debonding agents include, but are not limited to, those disclosed in U.S. Pat. No. 4,432,833, U.S. Pat. No. 4,425,186, and U.S. Pat. No. 5,776,308, all of which are incorporated herein by reference in their entirety. One example of a debonding agent-treated cellulose pulp is FFLE+. Plasticizers for cellulose, which can be added to the pulp slurry prior to the formation of the wet laid sheet, can also be used to soften the pulp, but they work by a different mechanism than debonders. Plasticizers act on the cellulose molecules within the fiber to make the amorphous regions flexible or soft. The resulting fiber is characterized as soft. Because plasticized fibers lack stiffness, the ground pulp is easier to densify compared to fibers that are not treated with plasticizers. Plasticizers include, but are not limited to, polyhydric alcohols such as glycerin, low molecular weight polyglycols such as polyethylene glycol, and polyhydroxy compounds. These and other plasticizers are described and exemplified in U.S. Pat. No. 4,098,996, U.S. Pat. No. 5,547,541, and U.S. Pat. No. 4,731,269, all of which are incorporated herein by reference in their entirety. Ammonia, urea and alkylamines are also known to plasticize wood products that contain primarily cellulose (AJ Stamm, Forest Products Journal 5(6):413, 1955, which is incorporated herein by reference in its entirety).

[0057] The nonwoven material of the present disclosure can include modified cellulose fibers. In some embodiments, one or more layers of the nonwoven material can include modified cellulose fibers of about 5 gsm to about 150 gsm, about 5 gsm to about 100 gsm, or about 10 gsm to about 50 gsm. In certain embodiments, one or more layers can include modified cellulose fibers of about 60 gsm, about 65 gsm, or about 70 gsm.

[0058] Synthetic In addition to the use of cellulosic fibers, the presently disclosed subject matter also contemplates the use of synthetic fibers. In one embodiment, the synthetic fibers include monocomponent fibers.

[0059] Monofilament fibers are typically commercially produced by melt spinning. In this procedure, each molten polymer is extruded through a die, e.g., a spinneret, which then pulls the molten polymer to remove it from the face of the spinneret. This is followed by solidification of the polymer by heat transfer to a surrounding fluid medium, e.g., cooling air, and then winding of the solid filaments. Non-limiting examples of further steps after melt spinning can also include hot or cold drawing, heat treatment, crimping, and cutting. This overall fabrication process is generally carried out as a discontinuous two-step process that first involves spinning the filaments and concentrating them into a tow containing multiple filaments. During the spinning step, some stretching of the filaments does occur as the molten polymer is pulled away from the face of the spinneret, which can also be called drawdown. This is followed by a second step in which the spun fiber is drawn or stretched to increase molecular alignment and crystallinity, giving the individual filaments enhanced strength and other physical properties. Subsequent steps may include, but are not limited to, heat setting, crimping, and cutting the filaments into fibers.

[0060] Monofilament fibers can also be formed in a continuous process where spinning and drawing are performed in a continuous process. During the fiber fabrication process, it is desirable to add various materials to the fiber after the melt spinning step at various subsequent steps in the process. These materials can be referred to as "finishes" and include active agents, such as, but not limited to, lubricants and antistatic agents. Finishes are typically applied via aqueous based solutions or emulsions. Finishes can impart desirable properties for both the fabricator of the fiber and the user of the fiber, for example, in airlaid or wetlaid processes.

[0061] Numerous other processes are involved before, during and after the spinning and drawing steps, see U.S. Pat. No. 4,950,541, U.S. Pat. No. 5,082,899, U.S. Pat. No. 5,126,199, U.S. Pat. No. 5,372,885, U.S. Pat. No. 5,456,982, U.S. Pat. No. 5,705,565, U.S. Pat. No. 2,861,319, U.S. Pat. No. 2,931,091, U.S. Pat. No. 2,989,798, U.S. Pat. No. 3,038, 235, U.S. Patent No. 3,081,490, U.S. Patent No. 3,117,362, U.S. Patent No. 3,121,254, U.S. Patent No. 3,188,689, U.S. Patent No. 3,237,245, U.S. Patent No. 3,249,669, U.S. Patent No. 3,457,342, U.S. Patent No. 3,466,703, U.S. Patent No. 3,469,279, U.S. Patent No. 3,500,498, U.S. Patent No. 3,585,685, U.S. Patent No. Nos. 3,163,170, 3,692,423, 3,716,317, 3,778,208, 3,787,162, 3,814,561, 3,963,406, 3,992,499, 4,052,146, 4,251,200, 4,350,006, and 4,370,114. Nos. 4,406,850, 4,445,833, 4,717,325, 4,743,189, 5,162,074, 5,256,050, 5,505,889, 5,582,913, and 6,670,035, all of which are incorporated herein by reference in their entireties.

[0062] The subject matter of the present disclosure can also include, but is not limited to, articles that include monofilament fibers that are partially oriented with varying degrees of drawing or stretching, highly oriented fibers, and mixtures thereof. The use of both partially oriented and highly oriented fibers in the same structure can be exploited to meet specific physical and performance properties based on how they are incorporated into the structure.

[0063] The fibers of the subject matter of the present disclosure are not limited in scope to any particular polymer, since any partially oriented fiber can provide enhanced performance in terms of elongation and strength. The extent to which the partially oriented fiber is oriented is not limited in scope, since different degrees of orientation provide different enhancements in performance. The scope of the subject matter extends to the use of partially oriented homopolymers such as polyester, polypropylene, nylon, and other melt-spinnable polymers. The nonwoven material of the present disclosure can include monofilament fibers. In certain embodiments, one or more layers of the nonwoven material can include monofilament fibers of about 5 gsm to about 150 gsm, about 5 gsm to about 100 gsm, or about 10 gsm to about 50 gsm. In certain embodiments, one or more layers can include monofilament fibers of about 60 gsm, about 65 gsm, or about 70 gsm.

[0064] In certain embodiments, the monofilament fibers are low dtex staple monofilament fibers ranging from about 0.5 dtex to about 20 dtex. In certain embodiments, the dtex value may range from about 1.3 dtex to about 15 dtex, from about 1.5 dtex to about 10 dtex, from about 1.7 dtex to about 6.7 dtex, or from about 2.2 dtex to about 5.7 dtex. In certain embodiments, the dtex value is 1.3 dtex, 1.5 dtex, 1.7 dtex, 2.2 dtex, 3.3 dtex, 5.7 dtex, 6.7 dtex, or 10 dtex.

[0065] Other synthetic fibers suitable for use in various embodiments as fibers include, but are not limited to, fibers made from various polymers, including, by way of example and without limitation, acrylics, polyamides (including but not limited to nylon 6, nylon 6 / 6, nylon 12, polyaspartic acid, polyglutamic acid), polyamines, polyimides, polyacrylics (including but not limited to polyacrylamide, polyacrylonitrile, esters of methacrylic acid and acrylic acid), polycarbonates (including but not limited to polybisphenol A carbonate, polypropylene carbonate), polydienes (including but not limited to polybutadiene, polyisoprene, polynorbornene), polyepoxides, polyesters (including but not limited to polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polycaprolactone, polyglycolide, polylactide, polyhydroxybutyrate, polyhydroxyvalerate, polyethylene adipate, polybutylene adipate, polypropylene succinate), polyethers (including but not limited to polyethylene glycol, polypropylene ... Polyolefins (including but not limited to polyethylene oxide), polybutylene glycol, polypropylene oxide, polyoxymethylene (paraformaldehyde), polytetramethylene ether (polytetrahydrofuran), polyepichlorohydrin), polyfluorocarbons, formaldehyde polymers (including but not limited to urea formaldehyde, melamine formaldehyde, phenol formaldehyde), natural polymers (including but not limited to cellulosics, chitosan, lignin, waxes), polyolefins (polyethylene Polyethylene (including but not limited to, polypropylene, polybutylene, polybutene, polyoctene), polyphenylenes (including but not limited to, polyphenylene oxide, polyphenylene sulfide, polyphenylene ether sulfone), silicon-containing polymers (including but not limited to, polydimethylsiloxane, polycarbomethylsilane), polyurethanes, polyvinyls (including but not limited to, polyvinyl butyral, polyvinyl alcohol, esters and ethers of polyvinyl alcohol, polyvinyl acetate, polystyrene, polymethylstyrene, polyvinyl chloride,Polyvinylpyrrolidone, polymethylvinylether, polyethylvinylether, polyvinylmethylketone, polyacetals, polyarylates, and copolymers (including but not limited to polyethylene-co-vinyl acetate, polyethylene-co-acrylic acid, polybutylene terephthalate-co-polyethylene terephthalate, polylauryllactam-block-polytetrahydrofuran), polybutylene succinate, and polylactic acid based polymers.

[0066] In other specific embodiments, the synthetic layer comprises synthetic filaments. The synthetic filaments can be formed by a spinning and / or extrusion process. For example, such a process can be similar to the methods described above with respect to the melt spinning process. The synthetic filaments can comprise one or more continuous strands. In some embodiments, the synthetic filaments can comprise polypropylene.

[0067] Binder The nonwoven material of the present disclosure may include a binder. In some embodiments, the nonwoven material may be coated with a binder on at least the outer surface. Such a binder may include carboxymethyl cellulose (CMC) and one or more metal salts, such as calcium chloride. In some embodiments, such a binder may include CMC, one or more metal salts, one or more surfactants, and one or more plasticizers. In certain embodiments, the binder may have a pH of about 4.3 to about 4.5.

[0068] Suitable binders include, but are not limited to, liquid binders and powder binders. Non-limiting examples of liquid binders include emulsions, solutions or suspensions of binders. Non-limiting examples of binders include polyethylene powders, copolymer binders, vinyl acetate ethylene binders, styrene-butadiene binders, urethanes, urethane-based binders, acrylic binders, thermoplastic binders, natural polymer-based binders, and mixtures thereof.

[0069] Carboxymethylcellulose (CMC) In some embodiments, the binder may be salt sensitive and water soluble. The binder may include a carboxymethyl cellulose (CMC) polymer. In certain embodiments, the binder may include sodium CMC or calcium CMC. The binder may further include a temporary wet strength agent, including but not limited to diallyl dimethyl ammonium chloride (DADMAC), polydiallyl dimethyl ammonium chloride (polyDADMAC), N-methylol acrylamide (NMA), polyacrylamide (PAM), glyoxylated polyacrylamide (GPAM), polyamide epichlorohydrin (PAE), polyamidoamine epichlorohydrin (PAAE), or combinations thereof. Other binders may include sodium CMC crosslinked with carboxylic acid, a cation sensitive binder, or a soluble starch. Any water soluble binder that is not significantly soluble in the miscible solution with low polarity should increase the strength, dispersibility, and shape retention suitable for use in the nonwoven material of the present disclosure.

[0070] In some embodiments, the binder is a cellulosic binder, such as CMC. In some embodiments, the CMC polymer may be anionic and water-soluble. In certain embodiments, the carboxymethylcellulose (CMC) may be Hercules Aqualon CMC (Ashland, Inc., Covington, KY) or Blanose 7L1C1 (Ashland, Inc., Covington, KY). In some embodiments, the nonwoven material of the present disclosure may comprise about 2% to about 15%, about 4% to about 12%, or about 5% to about 10% by weight of carboxymethylcellulose (CMC) based on the total weight of the nonwoven material. In certain embodiments, the nonwoven material of the present disclosure may comprise about 2%, about 5%, about 8%, about 10%, or about 15% by weight of carboxymethylcellulose (CMC) based on the total weight of the nonwoven material.

[0071] Metal salts In some embodiments, the binder may include one or more metal salts. Any polyvalent metal salt may be used, including transition metal salts. Non-limiting examples of suitable polyvalent metals include beryllium, magnesium, calcium, strontium, barium, titanium, zirconium, vanadium, chromium, molybdenum, tungsten, manganese, iron, cobalt, nickel, copper, zinc, aluminum, and tin. In some embodiments, the ions include aluminum, iron, and tin. In some embodiments, the metal ions have an oxidation state of +3 or +4. Any salts containing polyvalent metal ions may be used. Non-limiting examples of suitable inorganic salts of the above metals include chlorides, nitrates, sulfates, borates, bromides, iodides, fluorides, nitrides, perchlorates, phosphates, hydroxides, sulfides, carbonates, bicarbonates, oxides, alkoxides, phenoxides, phosphites, and hypophosphites. Non-limiting examples of suitable organic salts of the above metals include formates, acetates, butyrates, hexanoates, adipates, citrates, lactates, oxalates, propionates, salicylates, glycinates, tartrates, glycolates, sulfonates, phosphonates, glutamates, octanoates, benzoates, gluconates, maleates, succinates, and 4,5-dihydroxy-benzene-1,3-disulfonates. In addition to polyvalent metal salts, other compounds such as complexes of the above salts can be used, including, but not limited to, amines, ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DIPA), nitrilotriacetic acid (NTA), 2,4-pentanedione, and ammonia. In certain embodiments, the one or more metal salts can include calcium chloride (CaCl2). In some embodiments, the binder can comprise about 5% to about 35%, about 10% to about 30%, or about 15% to about 25% by weight of one or more metal salts based on the total weight of the carboxymethyl cellulose (CMC) binder. In certain embodiments, the nonwoven material of the present disclosure can comprise about 10%, about 15%, about 20%, about 25%, or about 30% by weight of one or more metal salts based on the total weight of the carboxymethyl cellulose (CMC) binder.

[0072] Surfactants In some embodiments, the binder can include one or more surfactants. These binders can have the surfactant incorporated therein during the fabrication process or can have the surfactant incorporated therein after fabrication and prior to application to the web. Such surfactants include, but are not limited to, the anionic surfactant Aerosol OT (Cytec Industries, West Paterson, NJ), which can be incorporated into the binder at about 0.75% by weight. In certain embodiments, the one or more surfactants can include Aerosol OT-75 (Cytec Industries, Inc., West Paterson, NJ). In some embodiments, the nonwoven material of the present disclosure can include about 0.5% to about 2.5%, about 0.75% to about 2.25%, or about 1% to about 2% by weight of the surfactant based on the total weight of the carboxymethyl cellulose (CMC) binder. In certain embodiments, the nonwoven material of the present disclosure can include about 0.75%, about 1%, about 1.5%, or about 2% by weight of the surfactant based on the total weight of the carboxymethyl cellulose (CMC) binder.

[0073] Plasticizer In some embodiments, the binder may include one or more plasticizers. Plasticizers may include, but are not limited to, polyhydric alcohols such as glycerin; low molecular weight polyglycols such as polyethylene glycols and polyhydroxy compounds. These and other plasticizers are described and exemplified in U.S. Pat. No. 4,098,996, U.S. Pat. No. 5,547,541, and U.S. Pat. No. 4,731,269, all of which are incorporated herein by reference in their entirety. By way of example and not limitation, the plasticizer may be polyethylene glycol 100 (PEG 100), polyethylene glycol 200 (PEG 200), polyethylene glycol 300 (PEG 300), or polyethylene glycol 400 (PEG 400). Ammonia, urea, and alkylamines are also known to plasticize primarily cellulose-containing wood products (AJ Stamm, Forest Products Journal 5(6):413, 1955, which is incorporated herein by reference in its entirety). In certain embodiments, the one or more plasticizers can include PEG 200 (CARBOWAX, Dow Chemical Co.). In some embodiments, the nonwoven material of the present disclosure can include about 0.05% to about 2.5%, about 0.1% to about 2.0%, or about 0.5% to about 1.5% by weight of the plasticizer based on the total weight of the nonwoven material. In certain embodiments, the nonwoven material of the present disclosure can include about 0.05%, about 0.1%, about 0.5%, about 1%, about 1.5%, or about 2.0% by weight of the plasticizer based on the total weight of the nonwoven material.

[0074] Binder Solution In certain embodiments, the binder may be an aqueous solution. The aqueous solution may include CMC and one or more metal salts. In certain embodiments, the one or more metal salts may include calcium chloride (CaCl2). In certain embodiments, the binder may be an aqueous solution including CMC, one or more metal salts, and one or more surfactants. The one or more metal salts may include calcium chloride (CaCl2). The one or more surfactants may include an anionic surfactant, such as Aerosol OT (Cytec Industries, West Paterson, NJ). In certain embodiments, the binder may be an aqueous solution including CMC, one or more metal salts, one or more surfactants, and one or more plasticizers. The one or more metal salts may include calcium chloride (CaCl2). The one or more surfactants may include an anionic surfactant, such as Aerosol OT (Cytec Industries, West Paterson, NJ). The one or more plasticizers may include polyethylene glycol, e.g., polyethylene glycol 200 (PEG 200) (CARBOWAX, Dow Chemical Co.).

[0075] In some embodiments, the binder can be applied as an emulsion in an amount ranging from about 1 gsm to about 15 gsm, about 2 gsm to about 10 gsm, about 2 gsm to about 8 gsm, or about 3 gsm to about 5 gsm. In some embodiments, the nonwoven material of the present disclosure can include about 2% to about 15%, about 3% to about 10%, or about 5% to about 8% by weight of the binder based on the total weight of the nonwoven material. In some embodiments, the nonwoven material of the present disclosure can include about 3%, about 5%, about 8%, or about 10% by weight of the binder based on the total weight of the nonwoven material. In some embodiments, the binder can be applied to the nonwoven material at an add-on rate of about 5% to about 25%, about 10% to about 20%, or about 10% to about 15%. In certain embodiments, the binder can be applied to the nonwoven material at an add-on rate of about 10%, about 13%, about 14%, or about 15%.

[0076] The binder, whether or not part of an emulsion, can be applied to one side of the fibrous layer. In some embodiments, the binder can be applied to the exterior facing layer. Alternatively, the binder can be applied in equal or disproportionate amounts to both sides of the layer.

[0077] Binder characteristics In certain embodiments, the binder can have a ratio of carboxymethylcellulose (CMC) to metal salt of about 1:1 or about 3:1.

[0078] In certain embodiments, the binder can have a pH of about 4.3 to about 4.5, about 4.3 to about 4.4, or about 4.4 to about 4.5. In certain embodiments, the binder can have a pH of about 4.3, about 4.35, about 4.37, about 4.39, about 4.4, about 4.45, or about 4.5.

[0079] Liquid additives - Lotions and alcohol The nonwoven materials of the present disclosure can be pre-moistened with one or more liquid additives, such as a lotion, in some embodiments, the lotion can further include one or more alcohols.

[0080] In some embodiments, the nonwoven material may include one or more cationic lotions or one or more anionic lotions. In some embodiments, the one or more cationic lotions may have a pH of about 5 to about 8, about 7 to about 8, about 7.5 to about 8, or about 7.76. In some embodiments, the one or more anionic lotions may have a pH of about 8 to about 9, about 8 to about 8.5, or about 8.18. In some embodiments, the one or more lotions may be applied to the nonwoven material in an amount of about 3 times or about 3.05 times the weight of the nonwoven material.

[0081] In some embodiments, the nonwoven material may include one or more lotions further comprising one or more alcohols. In certain embodiments, the one or more alcohols may be about 10%, about 20%, about 24%, about 26%, or about 29% ethanol. In certain embodiments, the one or more alcohols may be at least about 26%. In some embodiments, the one or more lotions comprising one or more alcohols may have a pH of about 7 to about 9, about 7 to about 8.5, or about 7 to about 8.

[0082] nonwoven material The subject matter of the present disclosure provides a nonwoven material. As embodied herein, the nonwoven material can include at least one layer, at least two layers, at least three layers, or at least four layers. In certain embodiments, the nonwoven material includes one layer.

[0083] As embodied herein, the nonwoven material may be an airlaid material.

[0084] In some embodiments, the nonwoven material can include a single layer comprising cellulose fibers. The layer can further comprise a second type of cellulose fibers. By way of example and not limitation, the cellulose fibers can include modified cellulose fibers, cellulose fluff, and / or eucalyptus pulp. Alternatively, the cellulose fibers of the layer can include only softwood fibers. Further alternatively, the cellulose fibers of the layer can include only modified cellulose fibers.

[0085] In some embodiments, the nonwoven material can include a single layer that includes synthetic fibers, such as monofilament fibers. The layer can further include other types of synthetic fibers. In certain embodiments, the synthetic fibers of the layer can include only monofilament fibers.

[0086] In some embodiments, the nonwoven material can have multiple layers. In such embodiments, the nonwoven material can include multiple layers that include cellulosic fibers. Alternatively, the nonwoven material can include multiple layers that include synthetic fibers. In some embodiments, the nonwoven material can include layers that include cellulosic fibers, synthetic fibers, or a combination thereof.

[0087] The nonwoven material can be coated with a binder on at least a portion of its outer surface. It is not necessary for the binder to be chemically bonded to any portion of the layer, but it is preferred that it remain in close association with the layer by coating, adhesion, precipitation, or any other mechanism so as not to migrate from the layer during normal handling of the layer. For convenience, the association between the layer and the binder discussed above can be referred to as a bond, and the compound can be said to be bonded to the layer. The binder can be applied in an amount ranging from about 1 gsm to about 15 gsm, from about 2 gsm to about 10 gsm, from about 2 gsm to about 8 gsm, or from about 3 gsm to about 5 gsm.

[0088] Overall, the first layer can have a basis weight of about 25 gsm to about 100 gsm, about 40 gsm to about 80 gsm, about 50 gsm to about 75 gsm, or about 55 gsm to about 65 gsm. In certain embodiments, the first layer can have a basis weight of about 54 gsm.

[0089] Method for producing a nonwoven material A variety of methods can be used to assemble the materials used in the practice of the presently disclosed subject matter to produce the material, including but not limited to traditional dry forming methods, such as airlaying and carding, or other forming techniques, such as spunlace or airlace. Preferably, the material can be prepared by an airlaid process, which includes but is not limited to the use of one or more forming heads that deposit raw materials of different compositions in a selected order in a manufacturing process that produces a product having distinct layers. This allows for great versatility in the variety of products that can be produced.

[0090] In one embodiment, the material is prepared as a continuous airlaid web. Airlaid webs are typically prepared by disintegrating or defibering a sheet of cellulose pulp, typically by a hammer mill, to produce individualized fibers. Rather than a pulp sheet of virgin fibers, recycled airlaid edge trimmings, as well as off-spec transitional material resulting from grade changes and other airlaid manufacturing waste, can be fed to the hammer mill or other disintegrator. The ability to thereby recycle manufacturing waste contributes to improved economics for the overall process. The individualized fibers, whether from virgin or recycled sources, are then pneumatically conveyed to the forming head of an airlaid web former. Several manufacturers make airlaid web formers suitable for use in the presently disclosed subject matter, including Dan-Web Forming of Aarhus, Denmark, M&J Fibretech A / S of Horsens, Denmark, Rando Machine Corporation, Macedon, NY (described in U.S. Pat. No. 3,972,092), Margasa Textile Machinery of Cerdanyola del Valles, Spain, and DOA International of Wels, Austria. Many of these formers differ in the way they open and air convey the fibers to the forming wire, but they are all capable of producing webs of the presently disclosed subject matter. Dan-Web forming heads include rotating or oscillating perforated drums that help keep the fibers separated until they are pulled by vacuum onto a foraminous forming conveyor or forming wire. In the M&J machine, the forming head is essentially a rotating rocker above a screen. The rotating rocker can include a series or group of rotating propellers or fan blades. Other fibers are opened, weighed and mixed in a fiber dosing system such as a textile feeder supplied by Laroche SA of Cours-La Ville, France.From the textile feeder, the fibers are pneumatically conveyed to the forming head of the airlaid machine where they are further mixed with comminuted cellulose pulp fibers from the hammer mill and deposited onto a continuously moving forming wire. If defined layers are desired, a separate forming head can be used for each type of fiber. Alternatively or additionally, one or more layers can be prefabricated before being combined with additional layers, if any. In some embodiments, the forming wire can be patterned such that at least one layer of the resulting nonwoven material is patterned.

[0091] The airlaid web is transferred from the forming wire to a calender or other densification stage to densify the web, increase its strength, and control the web thickness, if necessary. In one embodiment, the fibers of the web are then bonded by passing through an oven set at a temperature high enough to fuse the thermoplastic or other binder material contained therein. In a further embodiment, secondary bonding from the drying or curing of the latex spray or foam application occurs in the same oven. The oven is a conventional ventilated oven, can be operated as a convection oven, or the necessary heating can be achieved by infrared or even microwave irradiation. In certain embodiments, the airlaid web can be treated with further additives before or after heat curing. The airlaid web can optionally be embossed or otherwise patterned. The airlaid web can then be wound into a bale on a roller.

[0092] Uses and features of nonwoven materials The nonwoven material of the subject matter of the present disclosure can be used in any application known in the art. The nonwoven material can be used alone or as a component in other consumer products. For example, the nonwoven material can be used alone or as a component in various products, including cleaning products, such as personal care wipes, such as dispersible wet wipes. Such nonwoven materials have suitable strength and can be quickly dispersible in water at the same time.

[0093] The nonwoven material of the present disclosure can have improved mechanical properties. For example, the nonwoven material can be incorporated into a wipe, such as a wipe that is moistened with a lotion. The nonwoven material can have a cross direction (CD) wet tensile strength of greater than about 50 gli, greater than about 100 gli, or greater than about 200 gli, or greater than about 250 gli, or greater than about 300 gli, or greater than about 400 gli. In some embodiments, the nonwoven material can have a cross direction (CD) wet tensile strength of about 100 gli to about 500 gli, about 150 gli to about 450 gli, or about 200 gli to about 400 gli. In certain embodiments, the nonwoven material can have a cross direction (CD) wet tensile strength of about 100 gli, about 150 gli, about 200 gli, about 250 gli, about 300 gli, about 400 gli, about 450 gli, or about 500 gli. In some embodiments, the nonwoven material can have a wet tensile strength in the machine direction (MD) of greater than about 50 gli, greater than about 100 gli, or greater than about 200 gli, or greater than about 250 gli, or greater than about 300 gli, or greater than about 400 gli. In some embodiments, the nonwoven material can have a wet tensile strength in the machine direction (MD) of about 100 gli to about 500 gli, about 150 gli to about 450 gli, or about 200 gli to about 400 gli. In certain embodiments, the nonwoven material can have a wet tensile strength in the machine direction (MD) of about 100 gli, about 150 gli, about 200 gli, about 250 gli, about 300 gli, about 400 gli, about 450 gli, or about 500 gli. Additionally, the nonwoven material may have a wet elongation at peak load in the cross direction (CD) of greater than about 5%, greater than about 10%, or greater than about 13%, or greater than about 15%, or from about 10% to about 15%. In certain embodiments, the nonwoven material may have a wet elongation at peak load in the cross direction (CD) of greater than about 5%, about 6%, about 8%, about 10%, or about 15%. In some embodiments, the nonwoven material may have a wet elongation at peak load in the machine direction (MD) of greater than about 5%, greater than about 10%, or greater than about 13%, or greater than about 15%, or from about 10% to about 15%.In certain embodiments, the nonwoven material can have a wet elongation at peak load in the machine direction (MD) of about 5%, about 6%, about 8%, about 10%, or about 15%.

[0094] In some embodiments, the nonwoven material can have a cross direction (CD) dry tensile strength of about 500 gli to about 2500 gli, about 900 gli to about 2000 gli, or about 1000 gli to about 1500 gli. In certain embodiments, the nonwoven material can have a cross direction (CD) dry tensile strength of about 600 gli, about 700 gli, about 800 gli, about 1000 gli, about 1200 gli, or about 1500 gli. In some embodiments, the nonwoven material can have a cross direction (MD) dry tensile strength of about 500 gli to about 2500 gli, about 900 gli to about 2000 gli, or about 1000 gli to about 1500 gli. In certain embodiments, the nonwoven material can have a cross direction (MD) dry tensile strength of about 600 gli, about 700 gli, about 800 gli, about 1000 gli, about 1200 gli, or about 1500 gli. Further, the nonwoven material can have a cross direction (CD) dry elongation of about 2% to about 15%, about 2% to about 8%, or about 2% to about 5%. In certain embodiments, the nonwoven material can have a cross direction (CD) dry elongation of about 2%, about 3%, about 4%, about 11%, about 12%, about 13%, or about 14%. In some embodiments, the nonwoven material can have a cross direction (MD) dry elongation of about 2% to about 15%, about 2% to about 8%, or about 2% to about 5%. In certain embodiments, the nonwoven material can have a cross direction (MD) dry elongation of about 2%, about 3%, about 4%, about 11%, about 12%, about 13%, or about 14%.

[0095] The nonwoven materials of the present disclosure can become dispersible quickly, hi some embodiments, the nonwoven materials can disperse in water in less than about 20 seconds, less than about 18 seconds, less than about 15 seconds, less than about 10 seconds, or less than about 5 seconds. EXAMPLES

[0096] The following examples are merely illustrative of the subject matter of the present disclosure, and they should not be construed in any way as limiting the scope of the subject matter.

[0097] Example 1 CMC bonded nonwoven material (cellulose) - Wet strength This example provides preliminary wet strength and dispersibility testing of CMC-bonded nonwoven materials containing cellulose fibers. Binder formulations were prepared containing various carboxymethylcellulose (CMC) types combined with calcium chloride (CaCl2) as the metal ion. The binder formulations were applied to cellulose handsheets prepared using a CPF (cellulose pad former) to form hydrogen-bonded webs containing 100% cellulose fibers (SSK grade, 4725, from Georgia Pacific). The binder formulations were applied to various levels of nonwoven materials in various ways, including: (i) spraying CMC onto the web, drying, then spraying calcium chloride onto the web and drying a second time; (ii) spraying CMC onto the web, followed by spraying calcium chloride onto the web and then drying; and (iii) mixing CMC with calcium chloride and spraying the mixture onto the web and drying. The resulting webs were tested for wet strength and dispersibility and were either deficient in wet strength, dispersibility, or both.

[0098] The binder was a 1000 mL solution of carboxymethylcellulose (CMC) (Blanose 7L1C1) containing calcium chloride (CaCl2). The binder had a ratio of CMC to calcium chloride of approximately 3:1. The natural pH of the binder was approximately 4.9-4.95. Table 1A and Table 1B show the binder formulations.

[0099] [Table 3]

[0100] [Table 4]

[0101] To prepare the samples, one side of the sample material was sprayed with the binder solution, placed in a vacuum box for 3 seconds, and then dried in a ventilated oven at 135°C for 3 minutes. The second side of the sample material was then sprayed in the same sequence as above. The samples were prepared according to Table 2.

[0102] [Table 5]

[0103] Addition of cationic and anionic lotion agents The samples were tested for strength with the addition of cationic or anionic lotion using a Thwing-Albert EJA Series Tester. Each of the samples was approximately 1 inch wide and 4 inches long. Lotion was added at 3 times the mass of the sample. The cationic lotion had a pH of 7.76 and the anionic lotion had a pH of 8.18. Lotioned tensile strength was tested at various pH levels of the binder solution with CMC and calcium chloride as shown in Table 1A and Table 1B. Strength test parameters are shown in Table 3.

[0104] [Table 6]

[0105] The results are shown in Figure 1 and Table 4.

[0106] [Table 7]

[0107] As shown in Table 4 (Table 7) and FIG. 1, cationic and anionic lotions did not affect the wet strength of the nonwoven material by varying the pH of the CMC and calcium chloride binder solutions.

[0108] Cationic lotion containing alcohol Samples were tested for strength with the addition of cationic lotion containing various levels of alcohol (10% ethanol, 20% ethanol, 24% ethanol, 26% ethanol, and 29% ethanol). The cationic lotion was added at 3 times the mass of the sample. The cationic lotion had a pH of 7.76 without adjustment. The 10% ethanol and cationic lotion solution had a pH of 7.91. With the addition of 24-29% ethanol, the pH of the lotion ranged from 8-8.12. The 20% ethanol solution had a pH of 7.96. The 24% ethanol solution had a pH of 8. The 26% ethanol solution had a pH of 8.12. The 29% ethanol solution had a pH of 8.06. The lotioned tensile strength was tested at various pH levels of binder solutions containing CMC and calcium chloride, as shown in Table 1A and Table 1B. The binders had a ratio of CMC to calcium chloride of approximately 3:1. The pH of samples 1-5 was approximately 4.95.

[0109] The results are shown in Table 5 and Figures 2A and 2B. Figure 2A provides results for the addition of cationic lotion, 24% ethanol, 26% ethanol, or 29% ethanol. Figure 2B provides results for the addition of cationic lotion and 29% ethanol.

[0110] [Table 8]

[0111] Binders containing CMC and calcium chloride with the addition of lotion and alcohol at a certain pH range provided increased strength in the nonwoven material. Furthermore, as shown in Table 1B, compared to samples 1-4 (pH 4.4) and 1-3 (pH 3.8), sample 1-5 (pH 4.91) had decreased strength in 26% and 29% ethanol solutions. At 26% and 29% ethanol, sample 1-3 had tensile strengths of 205 gli and 308 gli, respectively, and sample 1-9 had tensile strengths of 291 gli and 412 gli, respectively. Sample 1-5 with pH 4.91 had significantly lower tensile strengths of 104 gli and 180 gli, respectively, at 26% and 29% ethanol. The suitable range for CMC and calcium chloride binder solutions is a pH of 4.3 to 4.5. As shown in Figures 2A and 2B, the strength of the nonwoven material is affected by the alcohol content. For CMC-based binders, binders with at least 26% alcohol increased performance in terms of tensile strength, and decreasing the water content in the lotion increased the lotioned tensile strength. Further samples were tested with 80% ethanol on nonwoven materials containing cellulose fibers, resulting in a lotioned strength of about 800 gli.

[0112] Through further experimental work, it was found that satisfactory wet strength and dispersibility were simultaneously achieved when the pH of the binder containing CMC and calcium chloride was between 4.3 and 4.5.

[0113] pH of lotion and pH of CMC / CaCl2 binder solution Samples were tested for strength using various pH levels of cationic lotion. Lotion tensile strength was tested at various pH levels of binder solutions containing CMC and calcium chloride as shown in Table 1A and Table 1B. Lotion was added at 3 times the mass of the sample.

[0114] The results are shown in Table 6 and Figure 3. Figure 3 excludes the results for sample 1-1.

[0115] [Table 9]

[0116] As shown in Table 6 and FIG. 3, cationic lotions with different pHs do not affect the wet strength at different pHs of binder solutions containing CMC and calcium chloride.

[0117] Example 2 CMC bonded nonwoven material (cellulose) - Wet strength and dispersibility This example provides wet strength and dispersibility testing of cellulosic and modified cellulosic nonwoven materials bonded with binders containing either carboxymethyl cellulose (CMC) or CMC and calcium chloride (CaCl2). Lotion was added at 3 times the mass of the sample. All binder solutions had a pH of about 4.4. Samples A-1 to A-10 contained cellulose fiber (SSK grade, 4725, from Georgia Pacific). Samples B-1 to B-10 contained modified cellulose fiber (FFLE). Samples A1-A5 and B1-B5 were bonded with binders containing carboxymethyl cellulose (CMC). Samples A6-A10 and B6-B10 were bonded with binders containing CMC and calcium chloride.

[0118] Samples containing cellulose fibers were prepared according to Table 7.

[0119] [Table 10]

[0120] Samples containing modified cellulose fibers were prepared according to Table 8.

[0121] [Table 11]

[0122] Strength Test The samples were tested for dry tensile strength and elongation, and lotioned tensile strength and elongation using a Thwing-Albert EJA Series Tester. Each of the samples was about 1 inch wide and about 4 inches long. Samples A-6 through A-10 were further tested for tensile strength and elongation using an anionic lotion.

[0123] Table 9 shows the strength test results for cellulosic materials.

[0124] [Table 12]

[0125] Table 10 shows the strength test results for the modified cellulosic materials.

[0126] [Table 13]

[0127] Figure 4 shows the strength results for all samples. The CMC based binder without calcium chloride and lotion did not give adequate strength. Tests using anionic lotion gave less strength than the cationic lotion (both with ethanol). The CMC based binder with calcium chloride in cationic lotion with ethanol gave adequate strength.

[0128] Dispersibility Test Samples A-6 to A-10, which comprised cellulosic nonwoven materials with CMC and calcium chloride binder (pH 4.40) in a cationic lotion containing ethanol, were further tested for dispersibility. All samples were completely dispersed within a few seconds of shaking in a container containing 700 mL of tap water.

[0129] Example 3 CMC bonded nonwoven materials using varying binder pH - strength and dispersibility This example provides dispersibility and strength (wet and dry) testing of nonwoven materials containing binder formulations at various pH levels. As shown in Table 11, the binders contained carboxymethylcellulose (CMC), calcium chloride (CaCl2) and water in the proportions and amounts shown. The ratio of CMC:CaCl2 in the binder was approximately 1:1.

[0130] [Table 14]

[0131] Samples 3-1 through 3-8 were prepared. The samples were cationized pulp fiber (CPF) handsheets containing cellulose fibers (Leaf River 4725, Georgia Pacific). One side of the handsheet was sprayed with the binder solution, placed in a vacuum box for 3 seconds, and then dried in a ventilated oven at 120°C for 3 minutes. The second side of the handsheet was then sprayed in the same sequence as above. The spray add-on rate was 13%. The binder formulation was made to deliver 7% CMC and 6% CaCl2 to the handsheet. Samples 3-1 through 3-4 contained binders containing carboxymethylcellulose (CMC), calcium chloride (CaCl2), and water, and were not pH adjusted (pH 6.65). Samples 3-5 through 3-8 contained binders containing carboxymethylcellulose (CMC), calcium chloride (CaCl2), and water, and were not pH adjusted (pH 4.35). Table 12 shows the sample preparation of samples 3-1 to 3-8.

[0132] [Table 15]

[0133] Dispersibility Test The samples were placed in a shaking box (set of three boxes) as described in the IWSFG PAS 3B:2017-Disintegration Test Methods-Slosh Box, which is incorporated herein by reference in its entirety. An 8 L volume of water was added to each box. The time to disperse (seconds) was measured. Five specimens of each sample were tested.

[0134] Strength Test The samples were tested for tensile strength and elongation in both dry and lotioned conditions using a Thwing-Albert EJA Series Tester. Each of the samples was approximately 1 inch wide and 4 inches long.

[0135] Table 13 shows the dispersibility test results.

[0136] [Table 16]

[0137] Table 14 shows the individual tensile strip strength test results for the pH 6.65 binder samples of this example.

[0138] [Table 17]

[0139] Table 15 shows the individual tensile strip strength test results for the pH 4.35 binder samples of this example.

[0140] [Table 18]

[0141] The average lotionized tensile strength for the samples was higher with the pH 4.35 binder (375 gli) than with the pH 6.65 binder (319 gli). Dispersibility results showed that samples containing both binders dispersed faster in the rocking box test.

[0142] Example 4 CMC bonded nonwoven materials (modified cellulose) - Wet strength and dispersibility This example provides wet strength and dispersibility testing of CMC-bonded nonwoven materials containing modified cellulose fibers. The modified cellulose fibers included cellulose fibers with aluminum precipitated as the metal ion. Each of the samples included three layers of modified cellulose fibers. Each of the samples included the same type of modified cellulose fibers. The binder was applied to the surface of the outer layer. Two different modified cellulose fiber types were tested: FFLE (sample 4-1) from Georgia Pacific Cellulose and Valance (sample 4-2) from International Paper. Each of the samples included a binder applied as a solution containing 9.75% CMC and 3.25% CaCl2 by weight of the total sheet, adjusted to a pH of 4.33, and containing 5% solids. Each sample was tested against a control containing unmodified cellulose fibers from Georgia Pacific Leaf River 4725.

[0143] Wet Strength Test Each sample was tested for wet strength as shown in Example 1. Figures 5A and 5B show the results for wet strength testing. As shown in Figure 5A, sample 4-2 (Valance) had a 37% increase in cross direction (CD) tensile strength compared to the control. As shown in Figure 5B, sample 4-1 (FFLE) had a 25% increase in machine direction (MD) tensile strength compared to the control. Sample 4-1 (FFLE) also had a 22% increase in cross direction (CD) tensile strength compared to the control.

[0144] The wet strength and dispersibility of the CMC bonded nonwoven material depended, at least in part, on the presence of suitable metal ions. The use of modified cellulose fibers with appropriate metal ions precipitated therein improved the wet strength and dispersibility properties of the CMC bonded nonwoven.

[0145] Example 5 CMC bonded nonwoven materials using surfactants and other additives (plasticizers) - Strength This example provides for the addition of various surfactants and other additives such as plasticizers to a CMC-based binder solution prior to application to a nonwoven material. The nonwoven material contained 100% cellulose fiber (SSK grade, 4725, from Georgia Pacific). The control included a nonwoven material bonded using a base solution containing 9.75% carboxymethylcellulose (CMC) and 3.25% calcium chloride by weight of the total substrate in a 5% solution, which was applied to the nonwoven material and dried. Sample 6-1 was a nonwoven material containing 100% cellulose fiber (SSK grade, 4725, from Georgia Pacific). Sample 6-1 was bonded using a base solution further containing a surfactant (Aerosol OT-75, from Cytec Industries, Inc.). The resulting mixture was applied to an unbonded nonwoven material and dried. Sample 6-2 was a nonwoven material containing 100% cellulose fibers (SSK grade, 4725, from Georgia Pacific). Sample 6-2 was bonded using a base solution containing 9.75% carboxymethylcellulose (CMC) and 3.25% calcium chloride by weight of the total substrate in a 5% solution, further containing a surfactant (Aerosol OT-75, Cytec Industries, Inc., 1.8% by weight of the total substrate in a 5% solution) and a plasticizer, polyethylene glycol (PEG) (PEG-200, CARBOWAX, Dow Chemical Co., 3.0% by weight of the total substrate in a solution containing 5% solids). The cellulose fibers were airlaid and the binder solution was sprayed onto both outer layers of the substrate.

[0146] The nonwoven materials were tested for wet strength and elongation as described herein, and the results of the strength and elongation tests are shown in Figures 6A and 6B.

[0147] The addition of surfactant to the base solution resulted in a CMC-bonded nonwoven material with comparable performance. The addition of surfactant also improved the softness of the nonwoven material as judged by a panel of users compared to a control nonwoven material containing untreated base solution. As shown in Figure 6B, the plasticizer improved the elongation of the nonwoven material. The addition of plasticizer was also observed to enhance the ability to wind the nonwoven material onto a roll.

[0148] In addition to the various embodiments described and claimed, the subject matter of the present disclosure is also directed to other embodiments having other combinations of the features disclosed and claimed herein. Thus, the specific features presented herein can be combined with each other in other ways within the scope of the subject matter of the present disclosure such that the subject matter of the present disclosure includes any suitable combination of the features disclosed herein. The above descriptions of specific embodiments of the subject matter of the present disclosure have been presented for purposes of illustration and description. They are not intended to be exclusive or to limit the subject matter of the present disclosure to those embodiments disclosed.

[0149] It will be apparent to those skilled in the art that various modifications and variations can be made in the systems and methods of the presently disclosed subject matter without departing from the spirit or scope of the presently disclosed subject matter. Thus, it is intended that the presently disclosed subject matter cover modifications and variations that come within the scope of the appended claims and their equivalents.

[0150] Various patents and patent applications are cited herein, the contents of which are incorporated herein by reference in their entireties.

Claims

1. 1. A nonwoven material comprising at least one layer comprising cellulose fibers, synthetic fibers, or a combination thereof, the at least one layer having at least a portion of a surface thereof coated with a binder, the binder comprising carboxymethyl cellulose (CMC) and a metal salt; said binder having a pH of 4.3 to 4.5; the nonwoven material comprises a lotion; The lotion comprises 24% to 29% ethanol.

2. 10. The nonwoven material of claim 1, wherein the binder has a pH of 4.3 to 4.

4.

3. 10. The nonwoven material of claim 1, wherein the binder has a pH of 4.4 to 4.

5.

4. 2. The nonwoven material of claim 1, wherein the CMC and metal salt are present in the binder in a ratio of 1±20%:

1.

5. 2. The nonwoven material of claim 1, wherein the CMC and metal salt are present in the binder in a ratio of 3±20%:

1.

6. 2. The nonwoven material of claim 1, wherein the metal salt is calcium chloride.

7. 10. The nonwoven material of claim 1, wherein the binder further comprises a surfactant.

8. 10. The nonwoven material of claim 1, wherein the binder further comprises a plasticizer.

9. 9. The nonwoven material of claim 8, wherein the plasticizer comprises polyethylene glycol.

10. 10. The nonwoven material of claim 1, wherein the cellulose fibers comprise modified cellulose fibers, cellulose fluff, eucalyptus pulp, or combinations thereof.

11. 10. The nonwoven material of claim 1, wherein the cellulosic fibers comprise softwood fibers, hardwood fibers, or a combination thereof.

12. 10. The nonwoven material of claim 1, wherein the synthetic fibers comprise bicomponent fibers.

13. The nonwoven material of claim 1, wherein the nonwoven material exhibits a wet strength of 6.757 N / 5 cm to 7.72 N / 5 cm.

14. A wipe comprising the nonwoven material of claim 1.

15. 13. A personal care product comprising the nonwoven material of claim 1.

16. A nonwoven material comprising at least one layer comprising cellulosic fibers, synthetic fibers, or a combination thereof, The at least one layer has at least a portion of its surface covered with a binder, the binder having a pH of 4.3 to 4.5, and the binder comprises carboxymethyl cellulose (CMC) and a metal salt in a ratio of 3±20%:

1.

17. The nonwoven material of claim 16, wherein the binder further comprises a surfactant and a plasticizer.

18. The nonwoven material of claim 16, wherein the binder further comprises at least one of a surfactant and a plasticizer.

19. The nonwoven material of claim 16, wherein the cellulose fibers comprise softwood fibers, hardwood fibers, or a combination thereof.

20. The nonwoven material of claim 16, wherein the nonwoven material exhibits a wet strength of 6.757 N / 5 cm to 7.72 N / 5 cm.

21. The nonwoven material comprising a lotion, 17. The nonwoven material of claim 16, wherein the lotion comprises 24% to 29% ethanol.

22. A personal care product comprising the nonwoven material of claim 16.

Citation Information

Patent Citations

  • Production of wet wipe

    JP1998046488A

  • Carboxymethyl cellulose salts and binding agent for disintegrable paper

    JP1999269201A

  • Multilayer product and its manufacturing method

    JP2006522234A

  • JPP388869B

  • Absorbent structure with integral vapor transmissive moisture barrier

    US20020013560A1